Knowledge Management Maturity Assessment in Finance and IT Department PT XYZ - Marlon Novie Akay; John Welly (Budapest International Research and Critics University, 2022)
The disruption of Covid-19 pandemic has brought Indonesia to experienced negative GDP growth for the first time since crisis in 1998. The pandemic stimulates the urgency to do things differently in the business sectors, including the FMCG business where the company needs to stay competitive and profitable in the tough market situation. One of the key success factors to survive in the competition is to keep innovating. A proper Knowledge Management implementation can help the Company to enrich the talent or people competencies and skills to contribute on business’ goals and innovation. PT. XYZ is one of the FMCG company in Indonesia that has a well-known iconic brand and wider market share. In managing the KM, there are few points noticed that can be further improved, such as the level of employee’s engagement with the KM tools, and lack of essential knowledge storage. The study purpose is to get understanding of KM maturity level and to propose the business solution. Methodology used is both quantitative (APO assessment framework) and qualitative (interview the function leads). The study shows that KM maturity level the Division is at level 4 or Refinement level, indicating that KM has been continuously improved and evaluated. However, to increase the maturity level up to mainstream level, there are three general business solutions proposed to be followed up by management, which are strengthening knowledge-based environment, improving the culture of knowledge sharing and innovation, and developing KM strategies and roadmap.